2019 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2019.pr.schipull
|View full text |Cite
|
Sign up to set email alerts
|

“Success Together”: Physics departmental practices supporting LGBTQ+ women and women of color

Abstract: Existing research on underrepresented/minority students focuses mainly on gender or race/ethnicity and ignores the intersection of identities of women of color and the experiences of lesbian, gay, bisexual, transgender, or queer (LGBTQ+) students. This research is also typically conducted at Predominately White Institutions. A large number of physics degrees earned by racial minorities have been earned from Minority Serving Institutions. This project examines the personal narratives of women of color, LGBTQ+ w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…They found that the physics students in their study placed high value on experiencing community membership and a sense of belonging, which supported them in continuing in the physics major. In a later study, this result was supported specifically for women of color and LGBTQ+ women, who described community membership as critical to their success [5].…”
Section: A Previous Work On the Identity Processmentioning
confidence: 87%
See 4 more Smart Citations
“…They found that the physics students in their study placed high value on experiencing community membership and a sense of belonging, which supported them in continuing in the physics major. In a later study, this result was supported specifically for women of color and LGBTQ+ women, who described community membership as critical to their success [5].…”
Section: A Previous Work On the Identity Processmentioning
confidence: 87%
“…Ong writes that individuals perform "complex social choreography" in order to achieve ordinariness. When existing in science spaces-traditionally white, male, and heterosexual-women of color must fight to be seen as competent members of the scientific community, making their social choreography especially dramatic [4,5,8].…”
Section: A Previous Work On the Identity Processmentioning
confidence: 99%
See 3 more Smart Citations